Precise and scalable fabrication of metal pair-site catalysts enabled by intramolecular integrated donor atoms. Issue 47 (25th November 2022) - Chen, Yuqing; Qiao, Shanshan; Tang, Yanhong; Du, Yi; Zhang, Danyu; Wang, Wenjie; Xie, Haijiao; Liu, Chengbin
Abstract : Biomass-derived nanocarbons with natural intramolecular N, S frameworks are impressively used to fabricate DACs with pairwise-dual-atoms on a gram-scale for highly efficient oxygen reduction reaction. Abstract : The precise configuration of metal pair sites at the atomic level in dual-metal single-atom catalysts (DACs) is key but challenging. Herein, we correlate the heteronuclear metal pair-site with the intrinsic structure of donor atoms in DACs, during which intramolecular heteroatoms, e.g., methionine, are shown adept at narrowing the atomic spacing of metal atoms to produce pairwise active sites. Then, guided by this "intramolecular coordinating confinement" strategy, the biomass-derived nanocarbon-containing native intramolecular N, S heteroatoms are impressively applied to fabricate DACs with N, S–carbon coordinated uniform (Cu, Mn) hetero-nuclear active pairs on a gram-scale (>5 g). The as-synthesized (Cu, Mn)/NSC electrocatalyst exhibits superior oxygen reduction reaction (ORR) activity, delivering a half-wave potential of 0.93 V vs. RHE in alkaline media and 0.78 V vs. RHE in acid media. The unique microenvironment in DACs for the ORR is deeply visualized by simulated calculations. This work provides a solution to challenges in controllable and scalable fabrication of DACs.